2020
DOI: 10.14581/jer.19010
|View full text |Cite
|
Sign up to set email alerts
|

Recent Aspects of Pediatric Epilepsy Surgery

Abstract: Surgery has been and is now a well-established treatment indicated for adults and children with drug-resistant epilepsy (DRE). The surgical landscape for children with DRE appears to be expanding, and surgical cases of pediatric epilepsy have increased significantly in the past decade, contrary to adult epilepsy. Several fundamental changes have led to the widespread surgical treatment for DRE in children, based on a risk-benefit analysis of pediatric epilepsy surgery, and a change in our overall approach to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…In the literature, mortality rates in pediatric epilepsy surgery tend to range from 1 to 2%, as reported by Kwon in 2019 [12]. Our study correlates these results with a mortality rate of 1.6% ( n = 1).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the literature, mortality rates in pediatric epilepsy surgery tend to range from 1 to 2%, as reported by Kwon in 2019 [12]. Our study correlates these results with a mortality rate of 1.6% ( n = 1).…”
Section: Discussionsupporting
confidence: 89%
“…It has been reported that the most common cause of pediatric epilepsy patients who undergo surgery is focal CD. The second most common cause is intracranial tumors [12]. Even though more patients with CD would be expected than intracranial tumors, the same number of cases were noted ( n = 11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generalized seizures, generalized multifocal encephalography, contralateral epileptiform activity, and MRI abnormalities are some of the conditions that indicate surgeries. 53 In patients with focal cortical dysplasia (FCD) during pretreatment evaluation, there might be a 30 to 40% chance of negative MRI results; however, in such cases, surgeries are also preferred. Poorly controlled seizures and negative therapeutic outcomes are contributing factors for surgical options.…”
Section: Role Of Epileptic Surgerymentioning
confidence: 99%
“…Recent advancements in presurgical evaluation and perisurgical management provide better opportunities for earlier surgeries. 53…”
Section: Role Of Epileptic Surgerymentioning
confidence: 99%